Methodology is perfection of sociocultural environment of institution of higher learning (International relations and international law Journal, 2016)
Intent attention to the questions of education, certain politics of the state in the field of education, requires from the teachers of new look to the process of education in modern educational establishment. Development of rising generation in modern Kazakhstan depends on that, how the sociocultural environment of educational establishments is arranged. Necessary principle of functioning of the system of trade education is providing of activity of institutions of higher learning as the special sociocultural institute, called to assist satisfaction of interests and necessities of students, developing their flairs in a spiritual, morally-humanistic and professional relation.
Keywords: student; sociocultural environment; independence; intellect; culture; professional competenses; after studies activity on education; educations of personality